Effects of salt- and oxygen-coupled stimuli on the reactive behaviors of hemoglobin-loaded polymeric membranes - Goh, Kek Boon (2020)
A high-performance polymeric membrane is usually associated with excellent electrochemical andmechanical behaviors. Thereby, this paper examines the effects of salt- and oxygen-coupled stimuli onreactive behaviors of hemoglobin-loaded polymeric membranes with varying initialfixed charge den-sities. For capturing the coupled chemo-electro-mechanical responses of the membrane, a multiphysicsmodel is mathematically formulated and then experimentally validated. The numericalfinding unveilsthat the Donnan potential strength of polyacidic membrane decreases with increase of ambient oxygenlevel, whereas the Donnan potential of present polyampholytic membrane, at neutral pH conditions, isalmost invariant towards changes of environmental salt concentration. When the environmental saltconcentration is smaller than the initialfixed charge concentration of the membrane, the surface con-ductivity of the system is enhanced bi-linearly with increase of the salt concentration due to weakenedDonnan potential strength acting over the polymer-solution, while the ion transport in the system isdominantly diffusion-governed if environmental salt concentration is greater than the initialfixed chargeconcentration of the membrane. Ultimately, thesefindings can be employed to systematically design andoptimize the dual salt-oxygen reactive hemoglobin-loaded polymeric membrane.